Who Pays for Clean Water? The Distribution of Water Pollution Control Costs / An Urban Systems Research Report - Hanneman William M; Lake Elizabeth E; Oster Sharon M (Westview Press, 1979)
Introduction, History of Water Pollution Control Legislation, Background Considerations, Municipal Expenditures, The Costs of Municipal Treatment Facilities, Federal and State and Local Government Fiscal Structures, Incidence of Various Methods of Financing Water Pollution Abatement, Survey of Local Governments Financing Water Pollution Control Expenditures, Incidence Calculations, The Results, The Incidence of Industrial Price Increases, Price Increases, Conclusions.